Effect of lipid parameters on carotid artery disease progression in patients undergoing carotid endarterectomy and unoperated patients with non-severe carotid artery stenosis - Özsin, Kadir Kaan; Sanrı, Umut Serhat; Toktaş, Faruk; Şeker, İbrahim Burak; Yavuz, Şenol (The European Research Journal, 2019)
Objectives: We aim to evaluate the relationship between serum lipid indices and carotid artery stenosis (CAS).Methods: This retrospective observational study included patients who underwent carotid endarterectomy (CEA) and unoperated patients who have CAS less than 50%. CAS was diagnosed with history and physical examination followed by doppler ultrasonography, coronary and carotid angiography. All data retrieved retrospectively from the hospital medical files. Non-high-density lipoprotein-cholesterol (non-HDL-C) level was calculated by removing HDL-C from total cholesterol. In addition, low-density lipoprotein-cholesterol (LDL-C)/HDL-C ratio, non-HDL-C/HDL-C ratio, and triglyceride (TG)/HDL-C ratio were assessed.Results: CEA group (77.5% male, mean age: 71.35 ± 8.35 years) included 40 patients who underwent CEA, and there were 32 patients who have less than 50% CAS in unoperated group (68.8% male, mean age: 63.94 ± 9.92 years). The development of CAS was not significantly correlated with LDL-C/HDL-C ratio (p = 0.119), non-HDL-C/HDL-C ratio (p = 0.227) and TG/HDL-C ratio (p = 0.768). Advanced age and presence of coronary artery disease were identified as an independent predictor of the development of CAS. For predicting development of CAS, there were 50.0% sensitivity and 65.6% specificity for LDL-C/HDL-C ratio and non-HDL-C/ HDL-C ratio (area under the curve [AUC]: 0.592, log rank p = 0.183, AUC: 0.583, log rank p = 0.227, respectively). Conclusions: We found that lipid ratios were not an independent predictors of the development of CAS. But, we think that AUC values which were above 0.5 for lipid ratios are may be important development of CAS.